EFL Learners’ Perceptions of Social Interaction on X (Twitter) for Second Language Acquisition - Olivia Pratnya Paramita; Ummi Nur Laila Sulistyani (Universitas Pahlawan Tuanku Tambusai, 2026)
Social media allows people to interact with others worldwide without face-to-face communication, creating opportunities for language learning through authentic online interaction. While previous studies have extensively examined language learning through social media platforms such as Facebook, Instagram, and TikTok, limited research has specifically explored how interactions on X (formerly Twitter) contribute to language acquisition, particularly from the perspectives of Indonesian EFL learners. This study aimed to explore Indonesian EFL learners’ perceptions of how Twitter interaction supports their language acquisition. Using a qualitative descriptive approach, the study involved 30 university students from different universities in Indonesia. Data were collected through questionnaires and semi-structured interviews and analyzed using thematic analysis. The findings revealed that learners perceived Twitter as a valuable platform for language acquisition. Through interaction on Twitter, learners improved their English proficiency, expanded their vocabulary, enhanced their exposure to authentic language use, and increased their confidence in communicating in English. Furthermore, Twitter features such as real-time interaction, discussion threads, and access to native speakers played significant roles in supporting learning. The study concludes that Twitter interaction facilitates language acquisition by providing meaningful exposure to authentic English communication and opportunities for active engagement with global users.